Preparation and Identification of Some New Pyridinium Salts - M. Shaker, Ameer; S. Shihab, Mehdi (Al-Nahrain Journal of Science, 2019)
In this work the pyridinium salts were prepared by two stage. The first step was preparation of Schiff bases compounds (A1-A5), The second step is preparation of pyridinium salts (B1-B5) by N-alkylation reaction between Schiff bases compounds and a proper alkyl halide(1,2-Chloroethane, 1-bromopropane, benzyl chloride, benzyl chloride andbromoethane). All the compounds were confirmed their structures by using spectroscopic techniques (FTIR and 1HNMR).